The Effect of Enriched Daphnia sp. with Different Source of Oil on the Survival Rate and the Growth of Oreochromis niloticus Larvae - I. Mokoginta; Dedi Jusadi; T.L. Pelawi (Jurnal Akuakultur Indonesia)
ABSTRACT